Applications of biochar in redox-mediated reactions - Yuan, Y.; Bolan, N.; Prévoteau, A.; Vithanage, M.; Biswas, J.K.; Ok, Y.S.; Wang, H. (Bioresource Technology, 2017)
Attached

Biochar is chemically more reduced and reactive than the original feedstock biomass. Graphite regions, functional groups, and redox-active metals in biochar contribute to its redox characteristics. While the functional groups such as phenolic species in biochar are the main electron donating moieties (i.e., reducers), the quinones and polycondensed aromatic functional groups are the components accepting electrons (oxidants). The redox capacity of biochar depends on feedstock properties and pyrolysis conditions. This paper aims to review and summarize the various synthesis techniques for biochars and the methods for probing their redox characteristics. We review the abiotic and microbial applications of biochars as electron donors, electron acceptors, or electron shuttles for pollutant degradation, metal(loid)s (im)mobilization, nutrient transformation, and discuss the underlying mechanisms. Furthermore, knowledge gaps that exist in the exploration and differentiation of the electron transfer mechanisms involving biochars are also identified.
Keywords: Biochar; Redox reactions; Functional groups; Graphite regions; Pyrolysis